2014
DOI: 10.1016/j.expneurol.2014.06.015
|View full text |Cite
|
Sign up to set email alerts
|

Associations between in vivo neuroimaging and postmortem brain cytokine markers in a rodent model of Wernicke's encephalopathy

Abstract: Thiamine (vitamin B1) deficiency, associated with a variety of conditions, including chronic alcoholism and bariatric surgery for morbid obesity, can result in the neurological disorder Wernicke’s encephalopathy (WE). Recent work building upon early observations in animal models of thiamine deficiency has demonstrated an inflammatory component to the neuropathology observed in thiamine deficiency. The present, multilevel study including in vivo magnetic resonance imaging (MRI) and spectroscopy (MRS) and postmo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
12
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 84 publications
4
12
0
Order By: Relevance
“…Further treatment (7 days of pyrithiamine + another EtOH exposure) caused a greater increase in volumes of lateral ventricles and CSF in the PE group. These findings in the PE group are consistent with enlargement of lateral ventricles observed with MRI in thiamine deficient rats (i.e., equivalent to the PS group in this study)(Dror et al 2010; Dror et al 2014; Zahr et al 2014a). In the previous studies, however, ventricular enlargement was more profound and appeared to persist (Dror et al 2010; Dror et al 2014), possibly because the length of thiamine deficiency was longer (14 days) and thiamine replacement was shorter (3 days)(Dror et al 2010; Dror et al 2014).…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Further treatment (7 days of pyrithiamine + another EtOH exposure) caused a greater increase in volumes of lateral ventricles and CSF in the PE group. These findings in the PE group are consistent with enlargement of lateral ventricles observed with MRI in thiamine deficient rats (i.e., equivalent to the PS group in this study)(Dror et al 2010; Dror et al 2014; Zahr et al 2014a). In the previous studies, however, ventricular enlargement was more profound and appeared to persist (Dror et al 2010; Dror et al 2014), possibly because the length of thiamine deficiency was longer (14 days) and thiamine replacement was shorter (3 days)(Dror et al 2010; Dror et al 2014).…”
Section: Discussionsupporting
confidence: 91%
“…Similarly, as has previously been reported in the literature of MRS case studies of WE (Mascalchi et al 2002; Murata et al 2001) and models of thiamine deficiency in rats treated with pyrithiamine hydrochloride (Lee et al 2001; Lee et al 1995; Pfefferbaum et al 2007; Rose et al 1993; Zahr et al 2014a), lower levels of both NAA and Cho were observed in pyrithiamine-treated relative to control rats. In the combined thiamine deficiency + EtOH exposure group, however, levels of Cho were not as low as in the thiamine deficiency group only.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…We observed that OEA reduces, not only IL‐1β and TNF‐α, but also MCP‐1 production. This finding may reveal unknown properties of OEA for the treatment of Wernicke's encephalopathy, a neuropsychiatric condition associated with alcoholism, because thiamine (vitamin B1) deficiency, a core element for the disorder, has been correlated with brain levels of MCP‐1 (Zahr et al ), which caused microglia recruitment/activation and exacerbated neurodegeneration (Yang et al ).…”
Section: Discussionmentioning
confidence: 99%
“…Experimental TD in rodents produces up‐regulation of cytokine genes and bioactive protein in vulnerable brain regions, including the thalamus and inferior colliculus (Karuppagounder et al., ; Vemuganti et al., ). Levels of chemokine/cytokine protein together with in vivo measures of pathology also had been determined in TD animal models to establish a relationship between neuroinflammatory and pathology markers (Zahr et al., ). After 12 days of PTD treatment, increased expression of chemokine/cytokine protein concentrations (MCP‐1, tumor necrosis factor‐α [TNF‐α], interleukin‐1β (IL‐1β), IL‐10, IL‐6) was observed in brain regions, such as inferior colliculi, thalamus, hypothalamus, anterior vermis, and hippocampus (Zahr et al., ).…”
mentioning
confidence: 99%